(untitled) (Cadernos de Sociomuseologia, 2023)
Article written within the scope of the FCT Carim project. Contemporary Art: A pathway towards Inclusive Museology. [FCT Exploratory Research Project, field: Arts, [FCT 2022.04615.PTDC, DOI 10.54499/2022.04615.PTDC]. This article aims to problematize the educational program that was carried out on the occasion of the exhibition "Heritage Artists and the Museum", which took place between February 1-28, 2022 at the Natural History Museum of Lisbon. The contemporary art collective exhibition and associated events aimed to reflect in a critical way on museums as ’media’ for information transmission. This article problematises the educative program, which combined metodologies from the disciplines of sociomuseology and education with the objective to develop inclusive and anti-hegemonic solutions for thinking and experiencing the ’display’ and museological content – for a non-specialised public and children. KEYWORDS: inclusive education; sociomuseology; learning action methods; schools; contemporary art; MUNHAC.